Factors associated with the modulation of pain by visual distortion of body size - Osumi, Michihiro; Imai, Ryota; Ueta, Kozo; Nakano, Hideki; Nobusako, Satoshi; Morioka, Shu (Frontiers in Human Neuroscience, 2014)
Modulation of pain using visual distortion of body size (VDBS) has been the subject of various reports. However, the mechanism underlying the effect of VDBS on pain has been less often studied. In the present study, factors associated with modulation of pain threshold by VDBS were investigated. Visual feedback in the form of a magnified image of the hand was provided to 44 healthy adults to examine changes in pain. In participants with a higher pain threshold when visual feedback of a magnified image of the hand was provided, the two-point discrimination threshold decreased. In contrast, participants with a lower pain threshold with visual feedback of a magnified image of the hand experienced unpleasant emotions toward the magnified image of the hand. Interestingly, this emotional reaction was strongly associated with negative body consciousness in several subjects. These data suggested an analgesic effect of visual feedback in the form of a magnified image of the hand is only when tactile perception is vivid and the emotional reaction toward the magnified image is moderate. The results also suggested that negative body consciousness is important for the modulation of pain using VDBS.